Successful Management of Pheochromocytoma Detected in Pregnancy by Interval Adrenalectomy in a VHL Patient - V. T. S. Kaluarachchi; Uditha Bulugahapitiya; Maulee Arambewela; Sonali Gunathilake (Case Reports in Endocrinology)
A 34-year-old mother with diabetes mellitus for 6 years presented in the late second trimester of her third pregnancy with new onset hypertension and characteristic hyperadrenergic spells. Clinical examination was unremarkable except a blood pressure of 170/110 mmhg. She had an elevated 24 hour urinary normetanephrine level with ultrasonic evidence of a hyperechoic hypervascular well-defined right supra renal mass of 6 x 5 cm in size which was very suggestive of a pheochromocytoma. Her management decisions were made by a multidisciplinary team which decided to deliver the baby by lower segment cesarean section (LSCS) as the pregnancy was advanced and to proceed with interval adrenalectomy after contrast enhanced computer tomography (CECT) of the abdomen with adrenal protocol. As a result a healthy baby was delivered by an uncomplicated elective LSCS at 36 weeks of POA. CECT abdomen with adrenal protocol confirmed a right-sided pheochromocytoma without any evidence of metastasis. Uncomplicated laparoscopic right adrenalectomy led to a clinical and biochemical recovery of the patient while histology confirmed the pheochromocytoma without any evidence of invasion. Subsequent follow up revealed cerebellar hemangioblastomas and retinal angioma in the right eye which led to a clinical diagnosis of Von Hippel Lindau disease (VHL). Even though clinical criteria for Von Hippel Lindau disease were fulfilled, her VHL genetic test was negative. At present she and her family are under surveillance of the endocrine team.